Not Another Article on the Author! God and Auteurs in Moving Image Analysis: Last Call for a Long Overdue Paradigm Shift. Issue 2 (December 2015) - Caston, Emily
Abstract : Many scholars in popular music and film studies accept the limitations of current film theories of authorship in relation to music video. This article moves the debate forward through a case study of the work of acclaimed music video director, Jamie Thraves. It focuses on three examples of his work: Jake Bugg's 'Two Fingers' (2012), Coldplay's 'The Scientist' (2002), and Radiohead's 'Just' (1995). Evidence of Thraves's close collaboration with the musicians in the scripting, shooting, and editing of each of these videos is used to investigate authorship in both domains of music and film production. The central argument of the analysis is about the conflicting expectations of power and control participants hold in the production process. These are based on a collision between historically distinct production cultures and intellectual property regimes. The article contributes to ongoing debates in the UK about moral rights, value, labour, and intellectual property in moving image production and argues that a paradigm shift for analysing creative production in music video is long overdue.